2018
DOI: 10.30958/ajp.5-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Socio-pragmatic Transfer in Egyptian Refusals

Abstract: Producing accurate and comprehensible language requires grammatical and syntactic knowledge; however, language accuracy does not ensure avoiding miscommunication which arises from the inappropriate use of speech acts. Thus, speech acts are among the prominent areas that have been investigated in the field of Inter-language pragmatics (ILP). Hence, the current study examines the realizations of the speech act of refusal by young adult Egyptian students in their L1 (Egyptian Arabic) and L2 (English). The study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, the Javanese metaphor is currently known among Javanese society as a mockery or a joke. In his research Darwis also confirmed indigenous socio-cultural knowledge in the foreign language (Darwish, 2018). Different kind of mitigation was found in the phrase 'may be' that mostly appear before the propositional utterances.…”
Section: Mitigating Taboo and Impositionmentioning
confidence: 73%
See 2 more Smart Citations
“…However, the Javanese metaphor is currently known among Javanese society as a mockery or a joke. In his research Darwis also confirmed indigenous socio-cultural knowledge in the foreign language (Darwish, 2018). Different kind of mitigation was found in the phrase 'may be' that mostly appear before the propositional utterances.…”
Section: Mitigating Taboo and Impositionmentioning
confidence: 73%
“…Some facts may provide the reason why it happened. These belong to non-structural factors that affect the emergent of pragmatic transfer, namely, as also found by Darwish (Darwish, 2018), some socio-cultural factors (Önal & Turgut, 2017) like home and host cultural schemas, degree of interaction (exposure) with the host society and other factors like host language proficiency, length of stay and motivation.…”
Section: The Pragmatic Transfer Tendencymentioning
confidence: 96%
See 1 more Smart Citation
“…In the Egyptian context, there are various studies that discussed the strategies related to linguistic transfer followed by EFL students (e,g. Darwish, 2018;Kharboush, 2016;Yousef, 1983). For instance, over a sample of 35 Egyptian secondary school students, Kharboush (2016) aimed at probing some discrepancies in the Egyptian secondary stage students" proficiency in translation, attributed to lexical and semantic transfer from Arabic to English, reflected through a set of language tasks.…”
Section: Figure (1) Classification Of Language Transfermentioning
confidence: 99%